Profiling the Mobile Customer: Privacy Concerns When Behavioural Advertisers Target Mobile Phones - King,Nancy; Jessen,Pernille W. (Computer Law and Security Review, 2010)
Mobile customers are increasingly confronted with behavioural advertising targeted individually on the basis of profiles generated by applying technologies to mine databases containing personally-identifying or anonymous data. This article is Part I of a two part series on “Profiling the Mobile Customer”. Part I answers the questions: “What is profiling in the context of behavioural advertising?” and “How will consumer profiling impact the privacy of mobile customers?”. The article examines the EU and U.S. regulatory frameworks for protecting privacy and personal data in regards to behavioural advertising that targets mobile customers. It identifies potential harms to privacy and personal data related to profiling for behavioural advertising. It evaluates the extent to which the existing regulatory frameworks in the EU and the U.S.provide an adequate level of protection. Consequently, the article identifies the privacy gaps in the regulatory frameworksthat will need to be addressed to adequately protect mobile consumers from profiling by marketers. Part II of Profiling the Mobile Customer that will appear in the next volume of the CLSR. It will discuss whether industry self-regulation or privacy enhancing technologies will be adequate to protect consumer privacy, or rather, whether new legislation will be necessary.
Keywords: Business Law